Latin American Society of Ethnobiology’s Code of Ethics - SOLAE Ethics Committee; Armando Medinaceli; Eréndira J. Cano; Arturo Argueta; Olga Lucia Sanabria (Ethnobiology Letters, 2018)
Latin American Society of Ethnobiology’s Code of Ethics